Signal-Induced Release of Guests from a Photolatent Metal-Phenolic Supramolecular Cage and Its Hybrid Assemblies - Park, Chiyoung; Yang, Beom Joo; Jeong, Ki Beom; Kim, Chae Bin; Lee, Seunghyun; Ku, Bon-Cheol (John Wiley & Sons Ltd., 2017)
The coordination chemistry of plant polyphenols and metal ions can be used for coating various substrates and for creating modular superstructures. We herein explored this chemistry for the controlled release of guests from mesoporous silica nanoparticles (MSNs). The selective adsorption of tannic acids (TAs) on MSN silica walls opens the MSN mesoporous channels without disturbing mass transport. The channel may be closed by the coordination of TA with Cu-II ions. Upon exposure to light, photolysis of Trojan horse guests (photoacid generators, PAGs) leads to acid generation, which enables the release of payloads by decomposing the outer coordination shell consisting of TA and Cu-II. We also fabricated a modular assembly of MSNs on glass substrates. The photoresponsive release characteristics of the resulting film are similar to those of the individual MSNs. This method is a fast and facile strategy for producing photoresponsive nanocontainers by non-covalent engineering of MSN surfaces that should be suitable for various applications in materials science.
Keywords: MESOPOROUS SILICA NANOPARTICLES; LAYER-BY-LAYER; CONTROLLED CARGO RELEASE; DRUG-DELIVERY; THIN-FILMS; PH; NETWORKS; MOLECULES; LIGHT; NANOCONTAINERS